Re‐Englishing 'flat‐world' fiction. Issue 1 (9th July 2019) - Pandey, Anjali
Abstract: Utilizing evidence from literary stylistics, and in keeping with the Kachruvian tradition, this paper makes the case for WE scholars to remain vigilant of the move away from the revolutionary heteroglossia and de‐Englishing strategies hallmarking literary creation and analyses of postcolonial writings from the margin – so apparent in Braj B. Kachru's works – to a current era of monoglossic inspired re‐Englishing strategies underpinning the post‐globalist enterprise of so‐called 'flat‐world' fiction in which under the guise of linguistic deterritorialization, center and periphery stratificational and spatialized arrangements emerge somewhat mitigated – even obfuscated. In the current post‐structuralist‐turn where contextual‐oriented rather than form‐focused analyses and the 'spatial turn' prevail, it is contested, Kachruvian‐spotlighted linguistic asymmetries still matter. Evidence is provided from emerging frameworks in the sociolinguistics of mobility, pedagogical linguistics, and political economy to demonstrate the intellectual staying power, and relevancy of Kachruvian frameworks for current sociolinguists.